STUDI EKSPLORASI DALAM KREATIVITAS FOOD PLATING DI RUMARI RESTAURANT JIMBARAN - Made Wahyuni; Trianasari; Luh Putu Triyanti Ariestiana dewi (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aims to examine the role of visual presentation and food plating in creating customer experience, supporting sustainable dining, and strengthening the brand image of Rumari Restaurant at Raffles Bali. The research uses a qualitative method through observation, interviews, and documentation involving chefs, kitchen staff, and trainees. The results show that food presentation is not only about appearance but also communicates values such as luxury, local identity, and environmental awareness. Visual elements like color, shape, and arrangement influence guests’ first impressions. In the concept helps build a unique identity while supporting sustainability. Creativity is encouraged but guided by standards to maintain consistency, and attractive presentation also promotes the restaurant through social media. Overall, food plating plays an important role in customer experience and brand image.